Controllable preparation and application of multi-scale oxidation-resistant copper powder

By adjusting the pH value of the solution and the content of the dispersant, combined with the secondary growth process and methacate ion covering layer, the problem of the traditional copper powder preparation and the lack of antioxidant resistance and the lack of antioxidant. preparation.

CN119346855APending Publication Date: 2025-01-24EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411487581.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional copper powder preparation technology cannot achieve precise control of particle size, and copper powder that has not been passivated by surface is prone to oxidation, resulting in a shortening of product life.

Method used

By adjusting the pH value of the solution, changing the content of the dispersant in the reducing agent, and adopting the secondary growth process, the thickness of the copper powder particle size and surface covering layer is used, and the use of methacate ions as the coordinating body in the cover layer to improve the anti -resistance to improve the anti -resistance Oxidation.

Benefits of technology

It achieves precise control of copper powder particle size and improved oxidation resistance, extending product life and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346855A_ABST
    Figure CN119346855A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy materials, and particularly relates to controllable preparation and application of multi-scale oxidation-resistant copper powder. A copper source solution and a reducing agent solution are mixed to adjust the pH value, and copper particles of 0.05-2 microns are prepared; when the dispersing agent is added into the reducing agent, the free chain of the polymer causes the copper crystal to aggregate and grow, and the copper powder of 3-5 microns is prepared; and the copper powder with the size of 7-10 microns is prepared by utilizing a secondary growth principle of crystals. And then the copper powder prepared through the three different methods is coated, and the copper powder with effective anti-oxidation coating is obtained. The nano-micron copper powder of various sizes is prepared by adjusting the pH value of the solution, changing the content of the dispersing agent in the reducing agent and through a secondary growth process on the basis, and the method has the advantages of being simple in technological process, low in cost, high in oxidation resistance, good in stability and the like; the conductive paste used for preparing the thick-film resistor element is well matched with an aluminum oxide substrate, and the average sheet resistance is 2-8 m omega / square.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new energy materials, and specifically relates to the controllable preparation and application of multi-scale antioxidant copper powder. Background Art

[0002] Copper paste has been widely used in the field of electronic component manufacturing in recent years, especially in MLCC, LTCC, flexible electronic paste, and power device conductive paste due to its good electrical conductivity, thermal conductivity and relatively low cost. Traditional conductive pastes often rely on precious metal materials such as silver and gold. Although they have good electrical conductivity, their high cost and possible electromigration at high temperatures limit their large-scale use and promotion. In order to further reduce production costs and improve material stability, copper paste, as a substitute for precious metals, has gradually become a key research and development direction.

[0003] However, although the traditional process can prepare copper powders of different particle sizes in batches, the process is complicated and cannot be precisely controlled. In addition, the prepared copper powder is easily oxidized without surface passivation, which greatly reduces the product life. Especially when the copper powder particle size is in the nanometer and submicron range, the product is highly active and easily oxidized and agglomerated; therefore, the development of a multi-scale small-size copper powder preparation process that can achieve precise size control, good dispersibility, strong oxidation resistance, and is suitable for large-scale production is of great significance for promoting technological progress in this field.

[0004] To solve the above problems, patent application CN117259780A discloses a method for preparing polyhedral submicron copper powder, and a submicron-grade copper powder with good dispersibility is obtained by adding a reducing agent solution three times, but the problem of simplification of the production process is not solved, and hydrazine hydrate is used, which has certain harm to the human body. Patent application CN101879606B discloses a method for preparing submicron copper powder by sulfuric acid chemical reduction, which uses highly active and low-cost hydrogen as a reducing agent, reduces costs, and improves yield, but the copper powder prepared by the invention is not surface treated, and the problem of poor oxidation resistance of copper is not solved. Patent application JP5872063B2 discloses a copper nanoparticle without a protective layer, which has good dispersibility and low-temperature sintering, but the size control is not refined, and the oxidation resistance cannot be guaranteed after the substrate is sintered.

[0005] Therefore, it is necessary to provide a method for preparing antioxidant copper powder that can accurately control the particle size, so that it can be better applied to copper-based components. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and provide a preparation method of controllable anti-oxidation copper powder and application thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] An antioxidant copper powder is characterized in that the copper powder particle size and the coating layer on its surface are regulated by adjusting the pH value of the solution, changing the dispersant content in the reducing agent and, on this basis, by a secondary growth process; the coating layer is composed of formate ions, which exist in the coating layer in the form of ligands.

[0009] A controllable preparation method of the present invention is to control the particle size by adjusting the pH value of the solution. Under acidic conditions, the nucleation rate of copper atoms is slow, and the particle size is often larger; under alkaline conditions, the nucleation rate is fast, and more copper crystal nuclei are generated, so the particles grow rapidly and the final particle size is smaller; when the dispersant content is increased, the solution viscosity increases, and the increase in polymer molecular chains makes the size of the copper particles larger; secondary growth is achieved by adding seed crystals to the solution, providing more nucleation sites, and obtaining large-sized copper; and formate as a coating layer has excellent oxidation resistance and has a good sintering matching shrinkage rate for common alumina substrates.

[0010] As the preferred technical solution:

[0011] The controllable anti-oxidation copper powder as described above is spherical copper with a particle size of 0.05 to 10 μm. In the anti-oxidation copper powder, the coating layer has a thickness of 3 to 10 nm.

[0012] The present invention also provides a method for preparing an antioxidant copper powder as described in any one of the above items, comprising the following steps:

[0013] (1) mixing a copper source, a dispersant and a solvent to obtain a precursor solution A;

[0014] (2) Based on step (1), a reducing agent and a solvent are mixed, stirred and the pH value of the solution is adjusted to obtain a solution B. During the reaction, the nucleation rate of copper atoms is affected due to different conditions, and copper particles of different particle sizes are finally formed; after centrifugation, collection and drying, 0.05-2 μm copper powder is obtained;

[0015] (3) On the basis of step (1), a reducing agent, a dispersant and a solvent are mixed and stirred to obtain a solution C; during the reaction, the content of the dispersant increases, the viscosity increases, and the increase in polymer molecular chains leads to the polymerization of copper crystals, and the size of the copper powder increases; after centrifugation, collection and drying, 3-5 μm copper powder is obtained;

[0016] (4) Based on step (3), copper powder and solvent are mixed to obtain seed crystal dispersion D, and the solution E is obtained by mixing and reacting with the above two solutions. During the reaction, the added seed crystals provide nucleation sites for copper atoms in the solution, thereby promoting the growth of copper. After centrifugation, collection and drying, 7-10 μm copper powder is obtained.

[0017] (5) Mix the alcohol solution and the organic amine solution, add copper formate and stir to obtain solution F; mix the prepared copper powder with the solution and react to obtain solution G, where the formate ions (HCOO - ) has lone pairs of electrons, which can form weak coordination bonds with the copper atoms on the surface of the copper particles, thereby passivating the surface and achieving an antioxidant effect;

[0018] (6) The solution G is centrifuged, washed and dried to prepare antioxidant copper powder.

[0019] As the preferred technical solution:

[0020] In the method as described above, in step (1), the mass ratio of the copper source, the dispersant, and the solvent is 1: (0.9-1.5): (25-32); preferably, the copper source includes any one or a combination of two of copper sulfate pentahydrate, anhydrous copper sulfate, copper chloride or copper acetate, preferably copper sulfate pentahydrate; the dispersant includes any one or a combination of at least two of polyvinyl pyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide or β-cyclodextrin, preferably polyvinyl pyrrolidone.

[0021] According to the method as described above, in step (2), the mass ratio of the reducing agent to the solvent is 1:(12.5-15.2); the reducing agent comprises any one of sodium hypophosphite, ascorbic acid, sodium borohydride or D-glucose or a combination of at least two thereof, preferably ascorbic acid; the mass ratio of the copper source, the dispersant and the reducing agent in the solution B is 1:(1.52-1.8):(2-2.5); the molar concentration of the copper source in the solution B is 0.1-1 mol / L; the mass concentration of the dispersant is 5-20 mmol / L; the mass concentration of the reducing agent is 0.5-4 mol / L; the reaction temperature is 60-90°C and the reaction time is 2-4 h.

[0022] According to the method as described above, in step (3), the mass ratio of the reducing agent, the dispersant and the solvent is 1: (1-1.8): (10-15); the dispersant includes any one of polyvinyl pyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide or β-cyclodextrin or a combination of at least two thereof, preferably polyvinyl pyrrolidone; the reducing agent includes any one of sodium hypophosphite, ascorbic acid, sodium borohydride or D-glucose or a combination of at least two thereof, preferably ascorbic acid; the mass ratio of the copper source, the dispersant and the reducing agent in the solution C is 1: (10-12.5): (2.5-3.1); the molar concentration of the copper source in the solution C is 0.05-0.5 mol / L; the mass concentration of the dispersant is 0.5-1 mol / L; the mass concentration of the reducing agent is 0.5-2 mol / L; the reaction temperature is 65-80°C and the reaction time is 1-2h.

[0023] As in the above method, in step (4), solutions A and C are consistent with those in step (3); the mass ratio of copper particles to solution in the seed crystal dispersion is 1:(20-40); preferably, the seed crystal is one of steps (2) and (3); the reaction temperature is 65-85°C and the reaction time is 1-2h.

[0024] According to the method described above, in step (5), the alcohol solution is one or more of ethylene glycol, propylene glycol, isopropanol, and methanol; the organic amine solution is one or more of 1,2-propylenetriamine, isobutanolamine, triethanolamine, and diisopropanolamine; the mass ratio of the alcohol solution, the organic amine solution, and copper formate is (40-45):(7.4-9):1; the molar ratio of copper atoms to formate ions is 1:(0.8-1.2) mol / L; the reaction temperature is 120-150°C, and the reaction time is 2-4h.

[0025] In the method as described above, in step (6), water is deionized water or ultrapure water; the power of ultrasonic treatment is 50-500 W, the stirring speed is 8000-9000 rpm, and the time is 5-20 min.

[0026] The present invention also provides a use of the anti-oxidation copper powder as described in any one of the above items, wherein the anti-oxidation copper powder is used as a conductive agent to prepare a conductive paste for an aluminum oxide substrate.

[0027] As the preferred technical solution:

[0028] In the application described above, the components and contents of the conductive paste are: 70-85wt% antioxidant copper powder, 0-5wt% glass powder, 13% organic carrier content, and 1% additive.

[0029] In the application as described above, the organic carrier is composed of 5 to 15 wt % of a resin and the remainder of an organic solvent; the resin is ethyl cellulose, polyethylene, polypropylene, polyurethane or polyimide and epoxy resin; the organic solvent is acetone, turpentine, terpineol, dihydroterpineol, ethylene glycol butyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate or dibutyl phthalate.

[0030] As in the application described above, the conductive paste is also printed on the surface of the alumina substrate, and then dried and sintered.

[0031] For the application as described above, the drying temperature is 120-140°C and the time is 10-30 min. The sintering process is: in a nitrogen atmosphere, the temperature is increased to 450-600°C at a heating rate of 1-10°C / min and then kept at this temperature for 30 min-1 h. After that, the binder is quickly debonded and cooled to room temperature in a nitrogen atmosphere.

[0032] In the application described above, the conductive copper paste and the alumina substrate have good sintering matching, the copper film has no warping and cracking, and the average square resistance of the copper film is 2 to 8 mΩ / square (i.e., 2 to 8 milliohms per square).

[0033] Principle of the invention:

[0034] An antioxidant copper powder is characterized in that the copper powder particle size and the coating layer on its surface are regulated by adjusting the pH value of the solution, changing the dispersant content in the reducing agent and, on this basis, by a secondary growth process; the coating layer is composed of formate ions, which exist in the coating layer in the form of ligands.

[0035] During the chemical reaction, the particle size is controlled by adjusting the pH value. The specific principle is: under acidic conditions, the reduction rate of copper ions is slow and the nucleation rate is low, resulting in fewer crystal nuclei, longer growth time, and larger copper particles. Under alkaline conditions, the reduction reaction rate is accelerated, the nucleation rate is higher, more small crystal nuclei are formed, the growth time is shorter, and smaller copper particles are eventually formed. When the dispersant content is increased, the solution viscosity increases, and the increase in polymer molecular chains makes the copper size larger. Secondary growth is achieved by adding seed crystals to the solution, providing more nucleation sites, and producing large-sized copper.

[0036] Using formate as a coating layer can effectively slow down the degree of oxidation. In the oxidation reaction, formate ions act as electron donors, providing electrons to enable oxidants (such as oxygen or peroxides) to obtain electrons and reduce, thereby preventing other substances from being oxidized. The dense coating layer formed can provide copper powder with good oxidation resistance. Copper slurry prepared with oxidation-resistant copper powder can be debonded at low temperature in an air atmosphere.

[0037] The copper paste prepared in the present invention can be co-fired with an alumina substrate to form a dense conductive pattern, and has a strong bonding force with the alumina substrate. The device prepared in the present invention has a high degree of sintering densification, and the internal stress distribution of the chip device after sintering is uniform and moderate, the square resistance is small, and the solder resistance is strong. The qualified rate of reliability tests such as heating aging and accelerated life is high.

[0038] Beneficial effects:

[0039] The invention controls the particle size by adjusting the pH value, changes the dispersant content in the reducing agent and uses a secondary growth process on this basis to obtain copper powder of 0.05-10 μm. The copper powder surface has a formic acid protective layer and has good oxidation resistance.

[0040] The conductive paste for alumina formed by uniformly mixing the prepared antioxidant copper powder with an organic carrier and glass powder (glass powder may not be added) can be debonded during the co-firing process; the conductive paste for alumina can form an alumina substrate with excellent comprehensive performance after being co-fired with a substrate.

[0041] The preparation method of the invention is simple, low in cost, non-toxic and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The present invention is a process flow chart for preparing antioxidant copper powder and preparing resistors using antioxidant copper powder.

[0043] Figure 2 The SEM morphology of the oxidation-resistant copper powder prepared in different embodiments; wherein, Figure 2 a is the SEM morphology of the oxidation-resistant copper powder of Example 1, Figure 2 b is the SEM morphology of the oxidation-resistant copper powder of Example 2, Figure 2 c is the SEM morphology of the oxidation-resistant copper powder of Example 3; Figure 2 d is the SEM morphology of the oxidation-resistant copper powder of Example 4; Figure 2 (e) is the SEM morphology of the oxidation-resistant copper powder of Example 5.

[0044] Figure 3 This is a TEM morphology of the oxidation-resistant copper powder prepared in Example 1; wherein, Figure 3 Figure a is the structural diagram of the antioxidant copper powder. Figure 3 (b) is the EDS C, O, and Cu element distribution diagram of the oxidation-resistant copper powder. DETAILED DESCRIPTION

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0046] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:

[0047] Average square resistance: Use ST2258C digital four-probe to test the square resistance of the copper film on the sintered alumina substrate. Adjust the four-probe measurement mode to the square resistance mode, place the sintered alumina substrate on the test bench, make the probe face the center of the copper film surface and slowly press down, after the copper film is completely pressed, close the loop and get the square resistance value. Test and calculate the average square resistance of 5 samples (i.e. alumina substrates) under the same preparation conditions.

[0048] Example 1

[0049] A method for preparing an oxidation-resistant copper powder, the preparation process is as follows Figure 1 As shown, the specific steps are as follows:

[0050] (1) Preparation of raw materials;

[0051] Copper source: copper sulfate pentahydrate;

[0052] Solvent: deionized water;

[0053] Dispersant: polyvinyl pyrrolidone K30;

[0054] Reducing agent: ascorbic acid;

[0055] Copper hydroxide: concentration is 1M;

[0056] Dilute sulfuric acid: concentration is 0.5M;

[0057] Alcohol solution: glycerol;

[0058] Amine solution: triethanolamine;

[0059] Potassium formate;

[0060] Anhydrous ethanol;

[0061] (2) 100 g of copper sulfate pentahydrate, 92.5 g of polyvinyl pyrrolidone K30 and 3 L of solvent were mixed to obtain solution A; 189 g of ascorbic acid and 1.25 L of solvent were mixed to obtain solution B; the pH was adjusted to 6 with sodium hydroxide / dilute sulfuric acid; solution A and solution B were mixed evenly, reacted at 65° C. for 2 h to obtain solution C; and 0.5 μm copper powder was obtained after being collected and dried;

[0062] (3) 50 g of potassium formate, 2 L of propylene glycol and 500 ml of triethanolamine were mixed to obtain solution D; the seed crystal solution and solution D were mixed and reacted at 145° C. for 3 h to obtain solution E;

[0063] (4) Solution E was transferred to a beaker, cooled to room temperature, and then naturally precipitated to remove the supernatant. The solution was then washed with deionized water and ethanol for three times, respectively, and dried in a vacuum oven at 60° C. for 3 h to obtain a submicron copper powder with antioxidant properties.

[0064] The SEM morphology of the finally obtained oxidation-resistant copper powder is as follows: Figure 2 As shown in a, the TEM structure diagram is as follows Figure 3 As shown in a, the TEM EDS C, O, and Cu element distribution diagram is as follows Figure 3 As shown in b, the antioxidant copper powder is composed of copper powder and a coating layer located on the surface thereof; the coating layer is composed of formate ions, which exist in the form of ligands in the coating layer, and the thickness of the coating layer is 4.9 nm.

[0065] An application of an oxidation-resistant copper powder, such as Figure 1 As shown, the oxidation-resistant copper powder prepared in this embodiment and the glass powder (component is SiO 2 ~B2 O 3 system; hemisphere point temperature is 600℃, transition temperature is 400±30℃, D50 particle size is 1-2μm, D100 particle size is less than 10μm) and an organic carrier are mixed and dispersed into a uniform conductive slurry by a high-speed planetary mixer and a three-roll grinder, and the conductive slurry is printed on the surface of an alumina substrate, and then dried and sintered in sequence to make electrodes of resistor components.

[0066] Among them, the content of each component in the conductive paste for resistors is: 80wt% of antioxidant copper powder, 5wt% of glass powder, 13% of organic carrier content, and 1% of additives; the organic carrier is composed of 15wt% of resin and the remainder of organic solvent; the resin is acrylic resin (the manufacturer is Guangzhou Youlike Chemical Co., Ltd., with a molecular weight of 17W); the organic solvent is pinene alcohol, butyl carbitol acetate, and butyl carbitol mixed in a ratio of 4:3:3.

[0067] For the application as described above, the drying temperature is 120-140°C and the time is 10-30 min. The sintering process is: in a nitrogen atmosphere, the temperature is increased to 450-600°C at a heating rate of 1-10°C / min and then kept at this temperature for 30 min-1 h. After that, the binder is quickly debonded and cooled to room temperature in a nitrogen atmosphere.

[0068] The resistor finally produced is composed of a copper film and an alumina substrate. The copper film has no warping or cracking, and the average square resistance of the copper film is 5mΩ / square.

[0069] Example 2

[0070] A method for preparing an oxidation-resistant copper powder, the preparation process is as follows Figure 1 As shown, the specific steps are as follows:

[0071] (1) Preparation of raw materials;

[0072] Copper source: anhydrous copper sulfate;

[0073] Solvent: deionized water;

[0074] Dispersant: polyvinyl pyrrolidone K30;

[0075] Reducing agent: glucose;

[0076] Copper hydroxide: concentration is 1M;

[0077] Dilute sulfuric acid: concentration is 0.5M;

[0078] Alcohol solution: ethylene glycol;

[0079] Amine solution: isobutanolamine;

[0080] Potassium formate;

[0081] Anhydrous ethanol;

[0082] (2) 75 g of anhydrous copper sulfate, 86.5 g of polyvinyl pyrrolidone K30 and 2.5 L of solvent were mixed to prepare solution A; 295 g of glucose and 1.5 L of solvent were mixed to prepare solution B; the pH was adjusted to 7 with sodium hydroxide / dilute sulfuric acid; solution A and solution B were mixed evenly, reacted at 65° C. for 3 h to obtain solution C; and 0.9 μm copper powder was collected and dried to obtain;

[0083] (3) 60 g of potassium formate, 1.25 L of ethylene glycol and 500 L of isobutanolamine were mixed to obtain solution D; the seed crystal solution and solution D were mixed and reacted at 150° C. for 2 h to obtain solution E;

[0084] (4) Solution E was transferred to a beaker, cooled to room temperature, and then naturally precipitated to remove the supernatant. The solution was then washed with deionized water and ethanol for three times, respectively, and dried in a vacuum oven at 60° C. for 3 h to obtain micron copper powder with antioxidant properties.

[0085] The SEM morphology of the finally obtained oxidation-resistant copper powder is as follows: Figure 2 As shown in b.

[0086] An application of an oxidation-resistant copper powder, such as Figure 1 As shown, the antioxidant copper powder prepared in this embodiment is mixed with glass powder and an organic carrier by a high-speed planetary centrifugal mixer and a three-roll grinder to form a uniform conductive paste, and then the conductive paste for resistors is printed on the surface of an alumina substrate, and then dried and sintered in sequence to form electrodes for resistor components.

[0087] Among them, the content of each component in the conductive paste for resistors is: 80wt% of antioxidant copper powder, 5wt% of glass powder, 13% of organic carrier content, and 1% of additives; the organic carrier is composed of 15wt% of resin and the remainder of organic solvent; the resin is acrylic resin (the manufacturer is Guangzhou Youlike Chemical Co., Ltd., with a molecular weight of 17W); the organic solvent is pinene alcohol, butyl carbitol acetate, and butyl carbitol mixed in a ratio of 4:3:3.

[0088] For the application as described above, the drying temperature is 120-140°C and the time is 10-30 min. The sintering process is: in a nitrogen atmosphere, the temperature is increased to 450-600°C at a heating rate of 1-10°C / min and then kept at this temperature for 30 min-1 h. After that, the binder is quickly debonded and cooled to room temperature in a nitrogen atmosphere.

[0089] The resistor finally produced is composed of a copper film and an alumina substrate. The copper film has no warping or cracking, and the average square resistance of the copper film is 4.5mΩ / square.

[0090] Example 3

[0091] A method for preparing an oxidation-resistant copper powder, the preparation process is as follows Figure 1 As shown, the specific steps are as follows:

[0092] (1) Preparation of raw materials;

[0093] Copper source: copper chloride;

[0094] Solvent: deionized water;

[0095] Dispersant: polyvinylpyrrolidone K50;

[0096] Reducing agent: ascorbic acid;

[0097] Copper hydroxide: concentration is 1M;

[0098] Dilute sulfuric acid: concentration is 0.5M;

[0099] Alcohol solution: ethylene glycol;

[0100] Amine solution: diethanolamine;

[0101] Potassium formate;

[0102] Anhydrous ethanol;

[0103] (2) 135 g of anhydrous copper sulfate, 150 g of polyvinyl pyrrolidone K50 and 5 L of solvent were mixed to obtain solution A; 350 g of ascorbic acid and 2 L of solvent were mixed to obtain solution B; the pH was adjusted to 8 with sodium hydroxide / dilute sulfuric acid; solution A and solution B were mixed evenly, reacted at 70° C. for 2 h to obtain solution C; and 2 μm copper powder was collected and dried to obtain;

[0104] (3) 90 g of potassium formate, 2.5 L of ethylene glycol and 1.5 L of diethanolamine were mixed to obtain solution D; the seed crystal solution and solution D were mixed and reacted at 150° C. for 4 h to obtain solution E;

[0105] (4) Solution E was transferred to a beaker, cooled to room temperature, and then naturally precipitated to remove the supernatant. The solution was then washed with deionized water and ethanol for three times, respectively, and dried in a vacuum oven at 60° C. for 1.5 h to obtain micron copper powder with antioxidant properties.

[0106] The SEM morphology of the finally obtained oxidation-resistant copper powder is as follows: Figure 2 As shown in c.

[0107] An application of an oxidation-resistant copper powder, such as Figure 1 As shown, the antioxidant copper powder prepared in this embodiment is mixed with glass powder and an organic carrier by a high-speed planetary centrifugal mixer and a three-roll grinder to form a uniform conductive paste, and then the conductive paste for resistors is printed on the surface of an alumina substrate, and then dried and sintered in sequence to form electrodes for resistor components.

[0108] Among them, the content of each component in the conductive paste for resistors is: 80wt% of antioxidant copper powder, 5wt% of glass powder, 13% of organic carrier content, and 1% of additives; the organic carrier is composed of 15wt% of resin and the remainder of organic solvent; the resin is acrylic resin (the manufacturer is Guangzhou Youlike Chemical Co., Ltd., with a molecular weight of 17W); the organic solvent is pinene alcohol, butyl carbitol acetate, and butyl carbitol mixed in a ratio of 4:3:3.

[0109] For the application as described above, the drying temperature is 120-140°C and the time is 10-30 min. The sintering process is: in a nitrogen atmosphere, the temperature is increased to 450-600°C at a heating rate of 1-10°C / min and then kept at this temperature for 30 min-1 h. After that, the binder is quickly debonded and cooled to room temperature in a nitrogen atmosphere.

[0110] The resistor finally produced is composed of a copper film and an alumina substrate. The copper film has no warping or cracking, and the average square resistance of the copper film is 3.8mΩ / square.

[0111] Example 4

[0112] A method for preparing an oxidation-resistant copper powder, the preparation process is as follows Figure 1 As shown, the specific steps are as follows:

[0113] (1) Preparation of raw materials;

[0114] Copper source: copper sulfate pentahydrate;

[0115] Solvent: deionized water;

[0116] Dispersant: polyvinylpyrrolidone K50;

[0117] Reducing agent: ascorbic acid;

[0118] Alcohol solution: glycerol;

[0119] Amine solution: triethanolamine;

[0120] Potassium formate;

[0121] Anhydrous ethanol;

[0122] (2) 125 g of copper sulfate pentahydrate, 400 g of polyvinyl pyrrolidone K50 and 6 L of solvent were mixed to obtain solution A; 378 g of ascorbic acid and 4 L of solvent were mixed to obtain solution B; solution A and solution B were mixed evenly, reacted at 65° C. for 2 h to obtain solution C; and 5 μm copper powder was collected and dried to obtain;

[0123] (3) 150 g of potassium formate, 6 L of propylene glycol and 1.5 L of triethanolamine were mixed to obtain solution D; the seed crystal solution and solution D were mixed and reacted at 145° C. for 3 h to obtain solution E;

[0124] (4) Solution E was transferred to a beaker, cooled to room temperature, and then naturally precipitated to remove the supernatant. The solution was then washed with deionized water and ethanol for three times, respectively, and dried in a vacuum oven at 60° C. for 3 h to obtain micron copper powder with antioxidant properties.

[0125] The SEM morphology of the finally obtained oxidation-resistant copper powder is as follows: Figure 2 As shown in middle d.

[0126] An application of an oxidation-resistant copper powder, such as Figure 1 As shown, the antioxidant copper powder prepared in this embodiment is mixed with glass powder and an organic carrier by a high-speed planetary centrifugal mixer and a three-roll grinder to form a uniform conductive paste, and then the conductive paste for resistors is printed on the surface of an alumina substrate, and then dried and sintered in sequence to form electrodes for resistor components.

[0127] Among them, the content of each component in the conductive paste for resistors is: 80wt% of antioxidant copper powder, 5wt% of glass powder, 13% of organic carrier content, and 1% of additives; the organic carrier is composed of 15wt% of resin and the remainder of organic solvent; the resin is acrylic resin (the manufacturer is Guangzhou Youlike Chemical Co., Ltd., with a molecular weight of 17W); the organic solvent is pinene alcohol, butyl carbitol acetate, and butyl carbitol mixed in a ratio of 4:3:3.

[0128] For the application as described above, the drying temperature is 120-140°C and the time is 10-30 min. The sintering process is: in a nitrogen atmosphere, the temperature is increased to 450-600°C at a heating rate of 1-10°C / min and then kept at this temperature for 30 min-1 h. After that, the binder is quickly debonded and cooled to room temperature in a nitrogen atmosphere.

[0129] The resistor finally produced is composed of a copper film and an alumina substrate. The copper film has no warping or cracking, and the average square resistance of the copper film is 6.5mΩ / square.

[0130] Example 5

[0131] A method for preparing an oxidation-resistant copper powder, the preparation process is as follows Figure 1 As shown, the specific steps are as follows:

[0132] (1) Preparation of raw materials;

[0133] Copper source: copper sulfate pentahydrate;

[0134] Solvent: deionized water;

[0135] Dispersant: polyvinylpyrrolidone K50;

[0136] Reducing agent: ascorbic acid;

[0137] Alcohol solution: glycerol;

[0138] Amine solution: triethanolamine;

[0139] Potassium formate;

[0140] Anhydrous ethanol;

[0141] (2) 100 g of copper sulfate pentahydrate, 360 g of polyvinyl pyrrolidone K50 and 5 L of solvent were mixed to obtain solution A; 342 g of ascorbic acid and 5 L of solvent were mixed to obtain solution B; 200 g of copper powder and 5 L of solvent were mixed to obtain seed crystal solution; the above three solutions were mixed evenly, reacted at 70° C. for 1 h to obtain solution C; and 8-10 μm copper powder was collected and dried to obtain;

[0142] (3) 120 g of potassium formate, 2.5 L of ethylene glycol and 1 L of isobutanolamine were mixed to obtain solution D; the seed crystal solution and solution D were mixed, and the reaction was maintained at 150° C. for 2 h to obtain solution E;

[0143] (4) Solution E was transferred to a beaker, cooled to room temperature, and then naturally precipitated to remove the supernatant. The solution was then washed with deionized water and ethanol for three times, respectively, and dried in a vacuum oven at 60° C. for 3 h to obtain micron copper powder with antioxidant properties.

[0144] The SEM morphology of the finally obtained oxidation-resistant copper powder is as follows: Figure 2 As shown in figure e.

[0145] An application of an oxidation-resistant copper powder, such as Figure 1 As shown, the antioxidant copper powder prepared in this embodiment is mixed with glass powder and an organic carrier by a high-speed planetary centrifugal mixer and a three-roll grinder to form a uniform conductive paste, and then the conductive paste for resistors is printed on the surface of an alumina substrate, and then dried and sintered in sequence to form electrodes for resistor components.

[0146] Among them, the content of each component in the conductive paste for resistors is: 80wt% of antioxidant copper powder, 5wt% of glass powder, 13% of organic carrier content, and 1% of additives; the organic carrier is composed of 15wt% of resin and the remainder of organic solvent; the resin is acrylic resin (the manufacturer is Guangzhou Youlike Chemical Co., Ltd., with a molecular weight of 17W); the organic solvent is pinene alcohol, butyl carbitol acetate, and butyl carbitol mixed in a ratio of 4:3:3.

[0147] For the application as described above, the drying temperature is 120-140°C and the time is 10-30 min. The sintering process is: in a nitrogen atmosphere, the temperature is increased to 450-600°C at a heating rate of 1-10°C / min and then kept at this temperature for 30 min-1 h. After that, the binder is quickly debonded and cooled to room temperature in a nitrogen atmosphere.

[0148] The resistor finally produced is composed of a copper film and an alumina substrate. The copper film has no warping or cracking, and the average square resistance of the copper film is 8mΩ / square.

Claims

1. A multi-scale antioxidant copper powder, characterized in that: The copper powder particle size ranges from nanometer to micrometer. The copper powder comprises an inner layer of copper powder and an outer coating layer, wherein the outer coating layer is present in the form of formate ions as ligands.

2. The oxidation resistant copper powder according to claim 1, characterized in that: The copper powder is spherical copper with a particle size of 0.05 to 10 μm; in the anti-oxidation copper powder, the coating layer has a thickness of 3 to 10 nm.

3. A method for preparing an oxidation-resistant copper powder as claimed in claim 1 or 2, characterized in that: The copper powder particle size and the antioxidant layer are regulated by adjusting the solution pH value, changing the dispersant content in the reducing agent, and on this basis, through a secondary growth process. The specific steps are as follows: (1) mixing a copper source, a dispersant and a solvent to obtain a solution A; (2) Based on step (1), a reducing agent and a solvent are mixed, stirred and the pH is adjusted to obtain a solution B; after centrifugation, collection and drying, a copper powder of 0.05 to 2 μm is obtained; (3) Based on step (1), a reducing agent, a dispersant and a solvent are mixed and stirred to obtain a solution C; after centrifugation, collection and drying, a copper powder of 3 to 5 μm is obtained; (4) Based on step (3), copper powder and solvent are mixed to obtain seed crystal dispersion D, and the solution is mixed and reacted with the above two solutions to obtain solution E; after centrifugation, collection and drying, 7-10 μm copper powder is obtained; (5) mixing the alcohol solution and the organic amine solution, adding copper formate and stirring to obtain solution F; mixing the prepared copper powder with the alcohol solution and reacting to obtain solution G; (6) The solution G is centrifuged, washed and dried to prepare antioxidant copper powder.

4. The method according to claim 3, characterized in that In step (1), the copper source includes any one of copper sulfate pentahydrate, anhydrous copper sulfate, copper chloride or copper acetate, or a combination of two of them; the dispersant includes any one of polyvinyl pyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide or β-cyclodextrin, or a combination of at least two of them; the solvent is deionized water; and the mass ratio of the copper source, the dispersant and the solvent is 1: (0.5-5): (20-50).

5. The method according to claim 3, characterized in that: In step (2), the mass ratio of the reducing agent to the solvent is 1:(10-25); the mass concentration of the copper source in the solution C is 0.05-5 mol / L; the mass concentration of the dispersant is 5-80 mmol / L; the mass concentration of the reducing agent is 0.1-5 mol / L; the temperature of the reaction is 60-95° C., and the reaction time is 2-4 h.

6. The method according to claim 3, characterized in that In step (3), the mass ratio of the reducing agent, the dispersant and the solvent is 1: (0.5-3): (10-15); the molar concentration of the copper source in the solution E is 0.02-1 mol / L; the mass concentration of the dispersant is 0.2-1 mol / L; the mass concentration of the reducing agent is 0.2-5 mol / L; the reaction temperature is 60-90° C., and the reaction time is 1-2 h; the drying temperature is 50-80° C., and the drying time is 8 h.

7. The method according to claim 3, characterized in that In step (4), solutions A and D are consistent with those in claim 6; the mass ratio of copper particles to solution in the seed crystal dispersion is 1:(15-50); the reaction temperature is 60-95°C and the reaction time is 1-2h.

8. The method according to claim 3, characterized in that In step (5), the mass ratio of the alcohol solution, the organic amine solution and the copper formate in the solution G is (30-50): (7-10): 1; the molar ratio of the copper atoms and the formate ions in the solution H is 1: (0.5-2) mol / L; the reaction temperature is 120-150° C., and the reaction time is 2-4 h.

9. Use of the method for preparing controllable nano-micron copper powder according to any one of claims 1 to 9 in preparing copper slurry, wherein the copper slurry can be used for thick film resistors, MLCC, and LTCC.

Citation Information

Patent Citations

  • Submicron copper powder and method for preparing same by sulfuric acid-process chemical reduction

    CN101879606B

  • Preparation method of polyhedral submicron copper powder

    CN117259780A

  • copper powder

    JP5872063B2

Cited By

  • Nanometer copper powder, electrode copper paste, buzzing piece and preparation method of buzzing piece

    CN121571636A